Physiological and morphological responses of Brachiaria spp. to flooding - Bernardino Dias Filho, Moacyr; Carvalho, Cláudio José Reis de (Pesquisa Agropecuaria Brasileira, 2000)
The physiological and morphological responses of the forage grasses Brachiaria brizantha cv. Marandu, B. decumbens and B. humidicola were compared for plants grown in pots under flooding and well-drained conditions for 14 days. Flooding reduced specific leaf area and biomass allocation to roots in all species and enhanced leaf senescence in B. brizantha and B. decumbens. Relative growth rate was reduced by flooding in B. brizantha and B. decumbens, but not in B. humidicola. Leaf elongation rate was unaffected by flooding in B. decumbens and B. humidicola, but declined in B. brizantha since the first day of flooding. Net photosynthesis and leaf chlorophyll content were reduced by flooding in B. brizantha; however, no flooding effect could be detected in the other two species. For all species, there was a close relationship between net photosynthesis and stomatal conductance under flooding. These results show that the studied species have distinct degrees of tolerance to flood, B. brizantha is intolerant, B. decumbens is moderately tolerant and B. humidicola is tolerant. Because leaf elongation rate was immediately depressed by flooding only in B. brizantha, this measurement could be appropriate as an early detection mechanism for relative flood tolerance in Brachiaria spp.